Метафора природи в поетичних текстах М. Рильського і Л. Костенко - Кравець, Л. (Культура слова, 2020)
Метафори природи у творчості українських поетів М. Рильського
і Л. Костенко – це маркер індивідуального стилю, засіб вираження
ключових художніх ідей та показник динаміки образної мови.
Найчастіше метафоричне вираження в поетичних текстах обох
митців мають традиційні для лірики образи природи. Більшість із
цих метафор відображають красу і досконалість навколишнього
світу та корелюють із концептами час, історія, пам’ять, воля,
свобода.
Метафори природи обох митців характеризуються синтезом
інтелектуалізму й емоційності. Вони оригінальні і водночас
зберігають зв’язок з традицією, виявляють ознаки певного
художнього стилю (романтизм, класицизм, реалізм). Динаміка
метафор природи виявляється в асоціативному і семантико-
граматичному ускладненні їхньої структури та розширенні функцій. Metaphors of nature are very important in the works of Ukrainian
poets M. Rylskyi and L. Kostenko. Metaphors of nature are a means of
expressing key artistic ideas and a marker of individual style, and an
indicator of the dynamics of figurative language. For M. Rylskyi and
L. Kostenko, nature is a source of inspiration and an object of poetic
image. Through the metaphorization of the concepts of nature, the authors
realize a wide range of ideas about the eternal problems of mankind.
Most often metaphorical expression in the poetic texts of M. Rylskyi
and L. Kostenko have traditional for the lyrics images of the seasons
(autumn, spring, summer, winter), flora (forest, individual trees (willow,
oak), atmospheric phenomena, rain, snow, fog, wind), parts of the day
(evening), reservoirs (river). A separate subject of metaphorization is
nature, the world as a whole. Most of these metaphors profile the beauty
and perfection of nature, but often have the semantics of time, memory,
recollection, will, freedom.
Metaphors of nature in the poetic texts of M. Rylskyi and L. Kostenko
are characterized by a synthesis of intellectualism and emotionality. In
the poetic texts of artists, they contribute to the realization of the author’s
intentions and at the same time preserve the connection with tradition
and show signs of a particular artistic style (romanticism, classicism,
realism). Metaphors of nature evolve with the development of language
creativity of artists, which is manifested in the associative and semanticgrammatical
complication of the structure and expansion of the functions
of these metaphors.